2017
DOI: 10.1371/journal.pone.0174562
|View full text |Cite
|
Sign up to set email alerts
|

Spatial disparity dynamics of ecosystem service values and GDP in Shaanxi Province, China in the last 30 years

Abstract: The regional policy in China is shifting from solely gross domestic product (GDP) orientation to development that is more balanced between economic growth and ecological protection, as well as achieving equality among regions. Using land use maps and the adjusted value coefficients to assess ecosystem service values (ESV) for the 1980s, 1995, 2000, and 2010, we estimated the ESV in Shaanxi Province for different years, and characterized the spatial and temporal distribution of ESV and GDP. The results demonstr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
12
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 49 publications
1
12
0
Order By: Relevance
“…Being aware of the contribution of ESV to green GDP in different regions can help the government develop different policies for different regions. Li and Ding [13] evaluated the variations of ESV and GDP for Shananxi province from the 1980s to 2010 and found that disparities in GDP were much higher than those of ESV, which is consistent with our results.…”
Section: Conclusion and Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…Being aware of the contribution of ESV to green GDP in different regions can help the government develop different policies for different regions. Li and Ding [13] evaluated the variations of ESV and GDP for Shananxi province from the 1980s to 2010 and found that disparities in GDP were much higher than those of ESV, which is consistent with our results.…”
Section: Conclusion and Discussionsupporting
confidence: 89%
“…It is obvious that green GDP accounting has become increasingly popular. Green GDP can be calculated by various methods concerning energy intensity, pollution intensity [7], environmental costs [6] and ecosystem service value [9,12,13]. Until now, using different methods to measure green GDP, comparing differences between green GDP and GDP and mapping the spatial distribution of green GDP have been widely studied concerning the historical value of green GDP.…”
Section: Introductionmentioning
confidence: 99%
“…Due to LULC changes and urbanization, most of these studies showed moderate to significant decrease in ESV [15,16,28,29,41,43] while others found almost no change [46]. Some studies have also revealed an increase in ESV [47][48][49][50]. Such variations in the services value are of the following reasons.…”
mentioning
confidence: 99%
“…However, Xie found that there is no linear relationship between the total ESV and GDP [5]. Li found that the ESV in cities of Shannxi Province increased slightly or remained stable with the growth of GDP [44]. However, all these studies did not control variables, which means that the relationship between ESVs and GDP also includes the impact of other socioeconomic factors on ESVs.…”
Section: Plos Onementioning
confidence: 98%